Diversion and Restorative Justice for Children Facing the Law - Priyana, I Wayan Awe Ditya; Wiratny, Ni Ketut; Suryana, Kadek Dedy (Pelopor Publikasi Akademika, 2025)
This research analyzes the implementation of diversion through a restorative justice approach in the handling of children facing the law (ABH) in the jurisdiction of the Bali Police. Using normative legal research methods with a qualitative approach, this study examines the effectiveness of the diversion mechanism based on Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. The results of the study show that the implementation of diversion in the Bali Police has succeeded in reducing the burden of cases in court while creating a more humane settlement. However, several obstacles were found such as limited understanding of the apparatus, inadequate support facilities, and public resistance to the concept of diversion. This study also identifies opportunities for the integration of Balinese local wisdom values in the mediation process. The implications of this study include three main aspects: (1) policy - the need to improve the technical guidelines of diversion, (2) practice - the importance of building the capacity of mediators, and (3) academic - contribution to the development of diversion models based on local culture. The findings of this study are expected to be a reference for the development of a more effective and fair juvenile criminal justice system.